Just Medicine : A Cure for Racial Inequality in American Health Care - Matthew, Dayna Bowen (Book collections on Project MUSE., 2018)
"Over 84,000 black and brown lives are needlessly lost each year due to health disparities, the unfair, unjust, and avoidable differences between the quality and quantity of health care provided to Americans who are members of racial and ethnic minorities and care provided to whites. Health disparities have remained stubbornly entrenched in the American health care system--and in Just Medicine, Dayna Bowen Matthew finds that they principally arise from unconscious racial and ethnic biases held by physicians, institutional providers, and their patients. Implicit bias is the single most important determinant of health and health care disparities. Because we have missed this fact, the money we spend on training providers to become culturally competent, expanding wellness education programs and community health centers, and even expanding access to health insurance will have only a modest effect on reducing health disparities. We will continue to utterly fail in the effort to eradicate health disparities unless we enact strong, evidence-based legal remedies that accurately address implicit and unintentional forms of discrimination, to replace the weak, tepid, and largely irrelevant legal remedies currently available. Our continued failure to fashion an effective response that purges the effects of implicit bias from American health care, Matthew argues, is unjust and morally untenable. In this book, she unites medical, neuroscience, psychology, and sociology research on implicit bias and health disparities with her own expertise in civil rights and constitutional law. Just Medicine offers us a new, effective, and innovative plan to regulate implicit biases and eliminate the inequalities they cause, and to save the lives they endanger."--